2002
DOI: 10.2320/matertrans.43.2543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen on the Mechanical Properties of Ti<SUB>50</SUB>Ni<SUB>25</SUB>Cu<SUB>25</SUB> Metallic Glass

Abstract: A number of studies on the internal friction of hydrogenated amorphous alloys have been recently performed in order to develop new high damping materials with mechanical strength higher than that of crystalline ones. In this work, effects of hydrogen on the mechanical properties such as fracture strength and internal friction have been investigated in a Ti 50 Ni 25 Cu 25 metallic glass. It is found that the Ti 50 Ni 25 Cu 25 metallic glass has high fracture strength even after absorbing hydrogen up to 24.7 at%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…5b shows the variation of the fracture strength of the alloys with the hydrogen content. The fracture strength for both alloys decreased as the hydrogen content increased, indicating a deteriorating effect of the hydrogen on the mechanical integrity, as reported for various hydrogenated Ti-and Zr-based amorphous ribbons [13,14,25,26]. Under uniaxial loading, the as-spun and hydrogenated low-Zr alloy ribbons exhibit superior strength in comparison to that of the high-Zr alloy composition.…”
Section: Resultsmentioning
confidence: 59%
“…5b shows the variation of the fracture strength of the alloys with the hydrogen content. The fracture strength for both alloys decreased as the hydrogen content increased, indicating a deteriorating effect of the hydrogen on the mechanical integrity, as reported for various hydrogenated Ti-and Zr-based amorphous ribbons [13,14,25,26]. Under uniaxial loading, the as-spun and hydrogenated low-Zr alloy ribbons exhibit superior strength in comparison to that of the high-Zr alloy composition.…”
Section: Resultsmentioning
confidence: 59%
“…The halo peak shifted to the lower angle with increasing hydrogen content, indicating that the volume expansion occurs as shown in the other amorphous alloys. 6,10,11) It should be noted that the morphology of the amorphous ribbons was changed after electrolytic hydrogenation. Figure 2 shows a change in the outer appearance of the hydrogenated (Ni 0:6 Nb 0:4 ) 70 Zr 30 alloy ribbon (hydrogen content of about 15 at%) stored in air at room temperature for various periods of time.…”
Section: Methodsmentioning
confidence: 99%
“…24) In order to employ these characteristic properties of amorphous alloys in the development of new hydrogen permeable membranes, [25][26][27][28] Sakaguchi et al and Adachi et al studied hydrogen permeability and hydrogen embrittlement of amorphous thin films of LaNi 5 hydrogen storage alloy. 29,30) Moreover, Hara et al studied hydrogen permeability and embrittlement of melt-spun amorphous Ni-Zr and Ni-M-Zr (M = Ti and Hf) alloys and reported that these alloys had enough mechanical strength without suffering from embrittlement although those hydrogen permeability was much lower than that of the Pd-Ag alloys.…”
Section: Introductionmentioning
confidence: 99%